Savings, Credit and Insurance: Household Demand for Formal Financial Services in Rural Ghana - Mirko Bendig; Lena Giesbert; Susan Steiner (German Institute of Global and Area Studies (GIGA), 2009)
This paper argues that the study of the demand for financial services in developing countries leaves out part of the story, if it looks at only one of the three elements of the so called finance trinity, i.e. savings products, loans, or insurances, as is largely done in the literature. In contrast to previous research, it is assumed that households' choice for any of these services is strongly interconnected. Therefore, the paper simultaneously estimates the determinants of household demand for savings, loans and insurances by applying a multivariate probit model on household survey data from rural Ghana. On the one hand, the estimation results confirm the common finding that poorer households are less likely to participate in the formal financial sector than better off households. On the other hand, there is empirical evidence that the usage of savings products, loans and insurances does not only depend on the socio-economic status of households, but also on various other factors, such as households' risk assessment and the past exposure to shocks. In addition, trust in the providing institution and its products appear to play a key role. – – Bei der Betrachtung der Nachfrage nach Finanzdienstleistungen in Entwicklungsländern spiegelt die bisherige Literatur nur einen Teil des Gesamtbildes wider, da sie sich hauptsächlich auf eines der drei Elemente der so genannten 'finance trinity' - Sparprodukte, Kredite und Versicherungen - beschränkt. Im Gegensatz dazu wird hier unterstellt, dass die Entscheidungen von Haushalten für oder gegen die Verwendung jedes dieser Produkte eng miteinander verknüpft sind. Deshalb werden die Determinanten für die Nachfrage nach Sparprodukten, Krediten und Versicherungen simultan geschätzt, und zwar mit Hilfe eines multivariaten Probit-Modells auf der Grundlage von Haushaltsdaten aus einem ländlichen Gebiet Ghanas. Einerseits stützen die Resultate frühere Erkenntnisse aus der Literatur, nämlich dass ärmere Haushalte mit geringerer Wahrscheinlichkeit als besser gestellte Haushalte am formalen Finanzmarkt teilnehmen. Andererseits belegen die empirischen Ergebnisse, dass die Verwendung von Sparprodukten, Krediten und Versicherungen nicht allein vom sozioökonomischen Status der Haushalte, sondern auch von verschiedenen anderen Faktoren, wie der Selbsteinschätzung der Risikosituation seitens der Haushalte und der Erfahrung von Schocksituationen in der Vergangenheit, abhängen. Zudem scheint das Vertrauen in die Finanzinstitution, ihre Produkte und Mitarbeiter eine entscheidende Rolle zu spielen.
Keywords: G20; O16; R22; 330; rural financial markets; financial services; Sub-Saharan Africa; Ghana